Thermophilic microbiome acclimation for enhanced anaerobic digestion of food waste: Optimization and performance evaluation - Hengxuan Shao; Chunle Yuan; Jingwen Qiang; Wei Hua; Yanling Cheng; Wanqing Wang (PLoS ONE, 2025)
Thermophilic anaerobic digestion (TAD) represents a promising approach for food waste (FW) treatment, offering significant advantages including accelerated reaction rates and increased volumetric biogas yield. However, the practical application of TAD is hindered by both the limited availability of thermophilic methanogenic consortia and heightened sensitivity to organic loading rate (OLR) fluctuations. In this study, a two-stage temperature shift strategy from mesophilic to thermophilic was implemented to establish a stable methanogenic community. The results showed that daily biogas yield increased steadily with rising fermentation temperature, reaching to a peak of 671.2 ml at 55 °C, which were 60.8% higher than that of mesophilic digestion. Microbial community analysis revealed that TAD increased the abundance of dominant hydrolytic bacteria ( e.g., Defluviitoga ) and hydrogenotrophic methanogen ( e.g., Methanoculleus ), consequently enhancing biogas production efficiency. Moreover, gradually increasing the OLR from 1.5 to 4 g VS/(L·d) significantly enhanced both biogas production and CH 4 content, achieving a peak daily biogas yield of 2264.8 ml with sustained CH 4 concentration stability (72–76%).